1975
DOI: 10.1083/jcb.67.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by colchicine of fibrinogen translocation in hepatocytes.

Abstract: Colchicine inhibits the secretion into plasma of lipoproteins (12,18), albumin (11), and other proteins (11) produced by the liver. Electron microscopy has shown that, after administration of colchicine, the electron-dense, nonsecreted lipoproteins accumulate in cytoplasmic vesicles (12) and also in the Golgi apparatus (18) of hepatocytes; however, the accumulation site of the electron-transparent, nonsecreted proteins is unknown. In the present report, we demonstrate that fibrinogen, an electron-transparent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…This conclusion is consistent with our findings in serum, in which the rate of rise in CRP concentration was markedly decreased after colchicine administration. Such an effect of colchicine on secretion of other hepatocyte-preduced plasma proteins has been shown (14)(15)(16)(17). Electron microscopic studies indicated that the perinuclear staining found in large numbers of cells after colchicine administration appeared to represent CRP-filled RER.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This conclusion is consistent with our findings in serum, in which the rate of rise in CRP concentration was markedly decreased after colchicine administration. Such an effect of colchicine on secretion of other hepatocyte-preduced plasma proteins has been shown (14)(15)(16)(17). Electron microscopic studies indicated that the perinuclear staining found in large numbers of cells after colchicine administration appeared to represent CRP-filled RER.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, since colchicine has been shown to inhibit secretion of a variety of plasma proteins by the cells in which they are synthesized (14)(15)(16)(17), the effect of administration of this drug upon cellular localization of CRP during acute inflammation was investigated.…”
mentioning
confidence: 99%
“…In the former period, between 1964 and 1980, most au thors working in this field described the fol lowing situation: in the normal state, a rela tively low percentage of hepatocytes (be tween 1 and 36% according to the protein) were actively engaged in synthesis, and plasma protein-synthesizing hepatocytes were randomly distributed in the hepatic lobule with sometimes a preferential locali zation around the portal triads or the centrilobular vein. For example, this was the case for albumin, some acute phase reactant pro teins such as C-reactive protein, a2-macroglobulin, ai-acid glycoprotein, haptoglobin, some coagulation proteins such as prothrom bin or fibrinogen and of ceruloplasmin and transferrin [1], However, even during this period, three observations did not fit well with these data: (1) when an increase in the hepatic synthesis of prothrombin [24], trans ferrin [25] or albumin [26] was induced, the percentage of hepatocytes engaged in the syn thesis of these three proteins increased strik ingly to shift from a small percentage to almost all hepatocytes; (2) inhibition of plasma protein secretion by microtubule-depolymerizing drugs, such as colchicine, which augment the amount of intracellular proteins, resulted in an increase in the num ber of fibrinogen-synthesizing hepatocytes [27], and (3) observation of serial liver sec tions clearly demonstrated that during an acute inflammatory reaction, the same hepa tocytes were able to synthesize at least four different acute phase reactant proteins at the same time [28], At the end of the 1970s, introduction of membrane-permeabilizing agents in immunocytochemistry completely changed the situation. As discussed pre As recalled in the introduction, hepato cytes, which synthesize the bulk of plasma proteins, are not specialized in the produc tion of a given plasma protein.…”
Section: Introductionmentioning
confidence: 99%
“…The change in differentiation of smooth endoplasmic reticulum caused by N-2-AAF is a long-term effect, in contrast to the reversible short-term effect reported for colchicine and fibrinogen. Colchicine causes a decrease in secretion of albumin accompanied by an accumulation in the Golgi apparatus (Dorling et al, 1975;Redman et al, 1975), while fibrinogen causes a decrease in secretion of albumin which is accompanied by an accumulation initially in the rough microsomes, but subsequently in the Golgi apparatus (Feldmann et al, 1975).…”
Section: Discussionmentioning
confidence: 99%